Democratic Confederalism and the Theory of History: Historical Ontologies of Political Alternative in Bookchin, Öcalan, and Graeber - Paci, Bernardo (PARTECIPAZIONE E CONFLITTO, 2025)
This paper aims to discuss the "historical ontology of political alternative" emerging from the work of Abdullah Öcalan by comparing it to the ones of two other authors: Murray Bookchin, who has notoriously influenced his thought, and David Graeber, whose interest for the Kurdish movement and the thought of Öcalan has been significantly overlooked so far. The analysis delves into how the three authors frame the conditions of possibility for the historical emergence of radical political alternatives. Special attention is given to the contrasts between Bookchin and Öcalan in this respect, with special attention to the couple continuity/discontinuity and archaic/modern, to their distinctive views of dialectics and of the articulation between the dialectical poles, and to the roles of consciousness and knowledge in their political and historical reflections. Additionally, it investigates the theoretical and political convergence between Öcalan and Graeber, focusing on the notions, respectively, of democratic civilisation and baseline communism.